KAJIAN EMPIRIKAL IDEALISM BERAGAMA SEBAGAI KONTEN BUDAYA DALAM JARGON NILAI PANCASILA - I Made Ariasa Giri (Purwadita : Jurnal Agama dan Budaya, 2018)
Multiculturalism and pluralism of Indonesian society are shown by their uniquecommunity structure, because they vary in various ways. The influence of Indonesian society’splurality based on religion, race and ethnicity can be divided into positive and negative influences.Idioms that must be more remembered and used as policy bases should be based on the conceptof Unity in Diversity. It means, even if one is in one unit, it must not be forgotten, that in fact thisnation is different in one plurality. Thus, diversity is a color in life, and these colors will beharmonious, beautiful if there is an awareness to always create and like harmony in life throughbeautiful unity which is realized through integrase. Negative influence, the emergence of excessiveprimordialism (primordialism) which colors social interaction so that disintegration or socialconflict arises. The cause of conflict between religious communities due to a lack of solidarityand tolerance in dealing with existing differences. As explained in the previous discussion. Andhow to deal with it by fostering an open attitude between the differences that exist but must stillhold fast to each other’s faith and beliefs.Keywords: Empirical Study, Religious of Idealism, Cultural, Pancasila